PENGEMBANGAN SISTEM DETEKSI KEBOCORAN PIPA AIR PADA RUMAH KOS BERBASIS WEB - Achmad Sulthon Hadi; sujono (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Water wastage in boarding houses is often caused by undetected pipe leakage due to the lack of real-time monitoring systems. This condition can lead to increased operational costs and potential structural damage. This study aims to develop a web-based water pipe leakage detection analysis system using Internet of Things (IoT) technology. The system utilizes an ESP8266 (microcontroller) and a water flow sensor to identify abnormal water flow patterns. Data is processed using PHP and MySQL and presented through a web-based dashboard in the form of graphs and tables. The system was developed using the Waterfall method. The results indicate that the system is able to accurately distinguish water flow characteristics. Based on blackbox testing, all functional features achieved 100% validity. The system successfully identifies a "Leakage Detected" status when continuous water flow exceeds the defined duration threshold without user activity and assigns a "Normal" status when the flow corresponds to typical usage patterns. This implementation proves to be effective as a monitoring tool for early detection and prevention of losses caused by water leakage.